Influence of Language on Colour Perception: A Simulationist Explanation - Loïc Paul Heurley; Audrey Milhau; Gabrielle Chesnoy-Servanin; Laurent P. Ferrier; Thibaut Brouillet; Denis Brouillet (Biolinguistics, 2012)
“How can perception be altered by language?” is the fundamental question of this article. Indeed, various studies have pointed out the influence of colour-related knowledge on object and colour perception, evoked by linguistic stimuli. Here the relevance of the simulationist approach is assumed in order to explain this influence, where the understanding of colour-related words or sentences involves a process of colour simulation that is supported by a neuronal network partially similar to the network involved in colour perception. Consequently, colour-related knowledge and colour perception can interact through a process of pattern interference. In support of this idea, studies are discussed showing priming effects between colour simulation and colour perception, but two limitations are also raised. Firstly, these works all used between-category colour discrimination tasks that allow the intervention of lexical processes that can also explain priming. Secondly, these works control the congruency link between prime and target at the level of ‘colour category’, and no demonstration is made of an influence at the level of specific hues. Consequently, the simulationist view of language/perception interactions seems an interesting way to thinking but more experimens are needed in order to overcome some limitations.